Outcomes of lenvatinib therapy in poorly differentiated thyroid carcinoma - Roque, João (2023)
Funding Information: Ricardo Rodrigues was granted with a PhD scholarship by iNOVA4Health Research Unit (UIDP/04462/2020; UI/BD/154256/2022). The remaining authors did not receive any specific grant from funding agencies in the public, commercial, or non-for-profit sectors. Publisher Copyright: © 2023 the author(s) Published by Bioscientifica Ltd.